ANALISIS KONSEP DAN KOMPONEN VISUAL DASAR POSTER â€œTOBACCO BREAK HEARTSâ€ - Yulius, Yosef; Hallim, Bobby (UNIVERSITAS INDO GLOBAL MANDIRI)
In line with the increasing public need for information about health, public service advertisements are one of the appropriate media to be used by activists in carrying out health promotion. Media as a source of information must be designed as well as possible, starting from the concept to the visual form. During its development, public service advertising media in Indonesia still needs to be developed so that its quality can be globally equal. Increasing the quality of public service advertising media will have a positive impact on the target of delivering messages in a persuasive manner, creativity and innovation must continue to be implemented. Based on this, the field of visual communication design is here to collaborate in designing public service advertising media as a problem solver. The design process cannot be done instantly, there are several processes that must be passed, such as the process of drafting the concept and visual layout. In compiling basic visual concepts and layouts, there are several aspects that need to be considered, including communication and visual aspects. The communication aspect is needed as a form of a detailed communication strategy in conveying information to audiences, while the visual aspect is needed as a form of good presentation in perceiving ideas so that the media is easily accepted and remembered by the audience. The qualitative research method is used in analyzing the public service advertisement poster media as the research object. This understanding is expected to be able to improve the quality of the media, especially public service advertisements engaged in the health sector.